2010
DOI: 10.1073/pnas.1001639107
|View full text |Cite
|
Sign up to set email alerts
|

L-amino acids catalyze the formation of an excess of D-glyceraldehyde, and thus of other D sugars, under credible prebiotic conditions

Abstract: Previous work by us, and others, has shown that the formation of amino acids on prebiotic earth with the geometric arrangement called the L configuration can be understood. Some meteorites of the carbonaceous chondritic type deliver unusual amino acids, with alpha-methyl groups, which have an excess of the L isomers. We previously showed that in decarboxylative transamination reactions under credible prebiotic conditions they produce normal amino acids that also have a preference for the L isomer, as is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 14 publications
3
58
0
Order By: Relevance
“…Predominantly L-handed amino-oxazolines-precursors to RNA-are formed from the reaction of amino-oxazole with glyceraldehyde at a 1% excess of the L-enantiomer in the presence of chiral amino acids [136]. After the emergence of L-RNA, L-amino acids could then have determined the handedness of the D-sugars we see in life today [137].…”
Section: Selectionmentioning
confidence: 99%
“…Predominantly L-handed amino-oxazolines-precursors to RNA-are formed from the reaction of amino-oxazole with glyceraldehyde at a 1% excess of the L-enantiomer in the presence of chiral amino acids [136]. After the emergence of L-RNA, L-amino acids could then have determined the handedness of the D-sugars we see in life today [137].…”
Section: Selectionmentioning
confidence: 99%
“…It is not the arabino-6 initially formed by this addition reaction that ends up as the pyrimidine ribonucleotides; if it were, then there would be no way to produce enantiomerically pure ribonucleotides unless a prebiotic route to enantiopure glyceraldehyde 5 existed. Routes to non-racemic glyceraldehyde can be envisaged [9], but obtaining this three-carbon sugar enantiopure looks very difficult. A means of enantioenrichment is, therefore, needed at some point in the synthetic route.…”
Section: Prebiotic Ribonucleotide Synthesis In a Subsystemmentioning
confidence: 99%
“…As we described [103], we found that L amino acids that we examined and that were likely ones on prebiotic earth did in fact catalyze the formation of an excess of D glyceraldehyde under credible prebiotic conditions. We performed simple aldol condensations of glycolaldehyde and formaldehyde in water solution with the L amino acids, including L -methyl valine.…”
Section: D-sugarsmentioning
confidence: 88%